Comparison of Dexamethasone Intravitreal Implant with Conventional Triamcinolone in Patients with Postoperative Cystoid Macular Edema. (3rd April 2017) - Mylonas, Georgios; Georgopoulos, Michael; Malamos, Panagiotis; Georgalas, Ilias; Koutsandrea, Chryssanthi; Brouzas, Dimitrios; Sacu, Stefan; Perisanidis, Christos; Schmidt-Erfurth, Ursula
ABSTRACT: Aims : To evaluate the efficacy of the treatment with intravitreal triamcinolone acetonide or dexamethasone intravitreal implant in patients with postoperative cystoid macular edema (PCME). Materials and Methods : Thirty eyes of 29 patients with PCME were randomized into two groups: one group initially received an injection of 4 mg triamcinolone; retreatment after 3 months was dependent on functional and anatomic outcome in a PRN regimen. The second group received a single injection of the dexamethasone intravitreal implant (Ozurdex). Patients were followed for 6 months. The main outcomes were best-corrected visual acuity (BCVA) and central millimeter retinal thickness (CMMT). Results : Mean BCVA improved significantly in both groups at 3 months ( p ≤ 0.05) and 6 months ( p ≤ 0.05) after treatment. There was no statistically significant difference between the two groups in visual acuity improvement at 3 months ( p > 0.05) or 6 months ( p > 0.05). Mean CMMT of both groups also decreased significantly after treatment at 3 and 6 months (both p ≤ 0.05) and the reduction was significantly superior in the triamcinolone group compared to ozurdex group at 1 week and 6 months ( p ≤ 0.05). All cases with intraocular hypertension were managed with IOP-lowering medication and no surgery was required during the study. One patient was excluded because of endophthalmitis in the triamcinolone group. Conclusion : Intravitreal triamcinolone and dexamethasone implant are both equally effective in increasing visual acuity in patients with PCME at a 6-month follow-up. However, macular edema seems to respond more rapidly with intravitreal triamcinolone, and 3-monthly repetitive injections maintain the reduction in retinal thickness better than a single dexamethasone implant at the first 6 months of follow-up period.